Performance Evaluation of Two Pan Furnace with Forced Draft Combustion for Jaggery Making - Singh, A K; Baboo, Bangali; Singh, R D (Journal of Agricultural Engineering, 2008)
A two pan furnace designed and commissioned at Indian Institute of Sugarcane Research, Lucknow for concentration of sugarcane juice so as to make jaggery was having a provision of natural draft combustion. In order to see the effect of forced draft combustion a forced draft system was installed in the furnace. Tests were conducted to compare the performance of the furnace under forced draft combustion as compared to natural draft. Temperatures were recorded at different points such as combustion chamber, boiling pan, gutter pan and flue gases. Rate of temperature increase was higher inside the combustion chamber, in the early phase, in case of forced draft combustion as compared to natural draft. It was found that the rate of increase of temperature in boiling pan was similar under both system of combustion up to 110 min of time. Thereafter, it was higher in case of forced draft and striking point for jaggery making was attained 10 minutes earlier as compared to natural draft combustion. There was a saving of 8% of the bagasse under forced draft system as compared to natural draft. The combustion efficiency' was increased by 2.6% in case of forced draft combustion.